Hashtags, Resistance, and Reform: The Global Rise of Digital Activism - Sudirman; Rosmilawati, Srie; Toun, Nicodemus R.; Riyanti, Nova (Sinergi International Journal of Communication Sciences, 2024)
This study explores the evolving role of digital activism in shaping public discourse and political mobilization through social media. It aims to assess how strategic digital tools such as hashtags, visual content, and storytelling facilitate collective identity and enhance civic engagement. Employing a narrative review methodology, the paper synthesizes empirical studies from multiple contexts including the Arab Spring, #BlackLivesMatter, and #EndSARS. Results reveal that social media enables real-time coordination, emotional resonance, and participatory communication that extend beyond traditional media boundaries. These campaigns are found to effectively generate pressure on policymakers and influence public opinion. However, systemic challenges persist. Studies indicate that algorithmic bias, digital surveillance, and censorship disproportionately affect activists, particularly in authoritarian regimes. Additionally, disparities in digital infrastructure and literacy contribute to uneven access and representation. The discussion highlights that while digital platforms serve as powerful tools, their impact is mediated by political, economic, and technological contexts. The study concludes by emphasizing the need for policy reforms that enhance digital inclusion, protect online freedoms, and ensure algorithmic accountability. Future research should address regional variations in digital mobilization and examine the interplay between online and offline activism. These insights contribute to a more comprehensive understanding of digital activism in a rapidly evolving communication landscape.